Bacterial cellulose nanocrystals or nanofibrils as Pickering stabilizers in low-oil emulsions: A comparative study - Pinto, Náyra O. F. (2024)
Supplementary data to this article can be found online at https://doi. org/10.1016/j.foodhyd.2024.110427.